1982
DOI: 10.1038/bjc.1982.145
|View full text |Cite
|
Sign up to set email alerts
|

Large-bowel carcinomas with different ploidy, related to secretory component, IgA, and CEA in epithelium and plasma

Abstract: Summary.-Immunofluorescence staining for carcinoembryonic antigen (CEA), secretory component (SC), and epithelial IgA was evaluated semiquantitatively in 85 large-bowel carcinomas in relation to degree of tumour differentiation, Dukes' stage, and plasma CEA level. The tumours were divided into a near-diploid (ND, 28) and an aneuploid group (AN, 57) by means of flow-cytometric DNA measurements. Expression of SC and IgA in neoplastic epithelium was positively related to differentiation in both groups. The AN t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…We have earlier reported similar proportions of aneuploidy in colorectal carcinomas from larger series of patients without ulcerative colitis (Rognum et al, 1982;1987b;Meling et al, 1991). Other studies have also reported similar proportions of aneuploid carcinomas in patients with ulcerative colitis (Hammarberg et al, 1984;Melville et al, 1988).…”
Section: Discussionsupporting
confidence: 59%
“…We have earlier reported similar proportions of aneuploidy in colorectal carcinomas from larger series of patients without ulcerative colitis (Rognum et al, 1982;1987b;Meling et al, 1991). Other studies have also reported similar proportions of aneuploid carcinomas in patients with ulcerative colitis (Hammarberg et al, 1984;Melville et al, 1988).…”
Section: Discussionsupporting
confidence: 59%
“…Preparation and staining of the single cell suspensions with ethidium bromide (Gohde & Dittrich, 1971) were performed as detailed elsewhere (Rognum et al, 1982b , 1983), where-as those with one or more peaks above that level were considered as being distinctly aneuploid (AN). The criteria used for splitting the tumours into a ND and an AN group have been described and discussed in detail previously (Rognum et al, 1982b).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…This notion has been confirmed in our study correlating the CEA expression status directly to data on survival in a large series of patients with long well documented follow-up periods. Rognum et al (1982), however, were not able to show a correlation between the intensity of CEA expression and differentiation of large bowel tumours. Moreover plasma CEA levels do not seem to correspond with the intensity of CEA immunoreactivity in individual patients (Lewis & Keep, 1981).…”
mentioning
confidence: 91%